The professional doctorate : a practical guide - John Fulton; Peter Smith (New York Palgrave Macmillan, 2013)
"Are you interested in studying for a professional doctorate but aren't sure what's involved? This book offers concrete, practical guidance for anyone wishing to study for a professional doctorate degree. Fully up-to-date and based on the latest developme
Keywords: Doctor of philosophy degree. Universities and colleges -- United States -- Graduate work. EDUCATION -- Reference. STUDY AIDS -- Professional. STUDY AIDS -- Study Guides. Universities and colleges -- Graduate work. United States. Promotion